Solutions of Class X Social Teacher in Overcoming Problems Regarding the Implementation of the Independent Curriculum at MAN 1 Mukomuko - Melia, Yenni; Wahyuni, Yanti Sri; M. Arifin; Fasihun, Nur (International Journal of Educational Research Excellence, 2025)
This research is motivated by changes in the Curriculum, where previously MAN 1 Mukomuko school used the 2013 Curriculum, then in 2022 a new Curriculum was implemented, namely the Merdeka Curriculum. This raises new problems, especially problems that occur during the process of implementing the Merdeka Curriculum. This study aims to analyze the solutions of class X social teachers at MAN 1 Mukomuko in implementing the Merdeka Curriculum. The theory used is the Talacott Parsons AGIL theory. The approach used is a qualitative approach with a descriptive type. The data collection technique is purposive sampling. The types of data are primary data and secondary data. The techniques used in data collection are document studies, observations and in-depth interviews. The data analysis used is interactive data analysis developed by Milles and Huberman. From the results of the study, it can be concluded, solutions to problems arising from the implementation of the independent curriculum include: 1. Using cooperative learning methods. 2. Photocopying textbooks 3. Learning using cellphones and media. 4. Independent learning 5. Reciprocal interaction patterns between students and teachers.